2018
DOI: 10.1016/j.atherosclerosis.2018.02.016
|View full text |Cite|
|
Sign up to set email alerts
|

Ankle brachial index and cognitive function among Hispanics/Latinos: Results from the Hispanic Community Health Study/Study of Latinos

Abstract: In addition to being a robust indicator of arterial compromise, our study suggests that abnormal ABI readings may also be useful for early signaling of subtle cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…We speculated that ABI may be associated with brain tissue blood perfusion, and could be a good indicator of cognitive function in elderly hypertensive patients. Although many studies have reported the association between the ABI and cognitive function [11][12][13][14], few studies have focused on the relationship between the ABI and cognitive function in elderly hypertensive patients. Our cross-sectional study found that the ABI was associated with cognitive impairment independent of age, gender, education, ASCVD history, blood pressure related parameters (PP and PI), and baPWV, and the cohort follow-up study also con rmed that cognitive function declined more rapidly in patients with a low ABI, revealing an association between the ABI and cognitive function in elderly hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that ABI may be associated with brain tissue blood perfusion, and could be a good indicator of cognitive function in elderly hypertensive patients. Although many studies have reported the association between the ABI and cognitive function [11][12][13][14], few studies have focused on the relationship between the ABI and cognitive function in elderly hypertensive patients. Our cross-sectional study found that the ABI was associated with cognitive impairment independent of age, gender, education, ASCVD history, blood pressure related parameters (PP and PI), and baPWV, and the cohort follow-up study also con rmed that cognitive function declined more rapidly in patients with a low ABI, revealing an association between the ABI and cognitive function in elderly hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] Studies have shown that the ABI could be a good indicator for cognitive impairment in community health population and patients with acute lacunar infarction or undergoing hemodialysis. [11][12][13][14] However, the relationship between ABI and cognitive function in elderly hypertensive patients has rarely been reported. According to the World Health Organization (WHO) age classi cation criteria for the elderly and the hypertension management guidelines, the elderly hypertensive patients can be divided into the young elderly hypertensive patients (60 ~ 75 years old) and the old elderly hypertensive patients (75 ~ 89 years old).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible reason why MD, and especially vegetables and fruits might be associated with reduced mental decline and distress is their protective effect on cardiovascular system (Billingsley and Carbone, 2018) and decrease in atherosclerosis build-up (Santhakumar et al , 2018). For example, the peripheral artery disease (arterial stenosis and stiffness) was negatively associated with the verbal learning and memory, verbal fluency, executive function and overall cognition (Tarraf et al , 2018). On the other hand, MD, especially when combined with moderate alcohol consumption, physical activity and non-smoking, was associated with a decreased risk of peripheral artery disease (Lopez-Laguna et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The ABI is a noninvasive measure of PAD (arterial stenosis and stiffness) [10]. The standard Doppler procedure using a Nicolet Doppler Elite 100R probe (Natus, Golden, CO) was used to measure the ABI, as described in previous studies [11].…”
Section: Measures Peripheral Arterial Disease (Pad)mentioning
confidence: 99%